Late presentation into care of HIV disease and its associated factors in Asia: Results of TAHOD - Jeong S. (2017)
© Mary Ann Liebert, Inc. 2016. Many HIV-infected individuals do not enter health care until late in the infection course. Despite encouraging earlier testing, this situation has continued for several years. We investigated the prevalence of late presenters and factors associated with late presentation among HIV-infected patients in an Asian regional cohort. This cohort study included HIV-infected patients with their first positive HIV test during 2003-2012 and CD4 count and clinical status data within 3 months of that test. Factors associated with late presentation into care (CD4 count < 200 cells/μl or an AIDS-defining event within ±3 months of first positive HIV test) were analyzed in a random effects logistic regression model. Among 3,744 patients, 2,681 (72%) were late presenters. In the multivariable model, older patients were more likely to be late presenters than younger (≤30 years) patients [31-40, 41-50, and ≥51 years: odds ratio (OR) = 1.57, 95% confidence interval (CI) 1.31-1.88; OR = 2.01, 95% CI 1.58-2.56; and OR = 1.69, 95% CI 1.23-2.31, respectively; all p ≤ 0.001]. Injecting drug users (IDU) were more likely (OR = 2.15, 95% CI 1.42-3.27, p < 0.001) and those with homosexual HIV exposure were less likely (OR = 0.45, 95% CI 0.35-0.58, p < 0.001) to be late presenters compared to those with heterosexual HIV exposure. Females were less likely to be late presenters (OR = 0.44, 95% CI 0.36-0.53, p < 0.001). The year of first positive HIV test was not associated with late presentation. Efforts to reduce the patients who first seek HIV care at the late stage are needed. The identified risk factors associated with late presentation should be utilized in formulating targeted public health intervention to improve earlier entry into HIV care.